ANALISIS LITERATUR TENTANG STRATEGI PEMBELAJAR IPS DALAM MENINGKATKAN PEMAHAMAN KONSEP SISWA SD - Bunga Giot Marito Sibaturara; Sinta Marito Purba; Luthfi Vivia Diwani; Khairunnisa; Kenza Amanda Sitohang; Mariani; Ruben Stevan Segar Situmeang (STKIP Subang, 2025)
Social Studies in elementary schools plays a strategic role in shaping students' knowledge, attitudes, skills, and social values. However, teaching practices are still dominated by lecture-based and teacher-centered methods, resulting in low conceptual understanding and critical thinking skills. This study aims to analyze effective and relevant IPS learning strategies in line with the demands of the Merdeka Curriculum. The research method used descriptive qualitative literature study through reviewing articles, books, research reports, and teaching practices. The results show that active strategies such as Project-Based Learning, contextual learning, cooperative models, multi-representation, and technology integration can increase student understanding by 27.5%–38.5% and active engagement by up to 87%. Discussion, simulation, debate, and linking material to real-world contexts were also proven effective in encouraging learning motivation. However, implementation faced challenges in the form of teacher limitations in differentiation, difficulties in formative-summative assessment, and limitations in interactive media. The conclusion of this study emphasizes the importance of active, varied, and contextual social studies learning. Implicitly, teachers need support in the form of training, interactive media, and authentic assessment guidelines so that social studies can truly shape a critical, adaptive, and characterful generation in line with the needs of the 21st century.